Changes in sialic acid binding associated with egg adaptation decrease live attenuated influenza virus replication in human nasal epithelial cell cultures. Issue 24 (2nd June 2021) - Powell, Harrison; Liu, Hsuan; Pekosz, Andrew
Abstract: Live Attenuated Influenza Virus (LAIV) is administered to and replicates in the sinonasal epithelium. Candidate LAIV vaccine strains are selected based on their ability to replicate to a high titer in embryonated hen's eggs, a process that can lead to mutations which alter the receptor binding and antigenic structure of the hemagglutinin (HA) protein. In the 2012–2013 northern hemisphere vaccine, the H3N2 HA vaccine strain contained three amino acid changes - H156Q, G186V and S219Y – which altered HA antigenic structure and thus presumably decreased vaccine efficacy. To determine if these mutations also altered LAIV replication, reabcombinant viruses were created that encoded the wild-type (WT) parental HA of A/Victoria/361/2011 (WT HA LAIV), the egg adapted HA (EA HA LAIV) from the A/Victoria/361/2011 vaccine strain and an HA protein with additional amino acid changes to promote α2, 3 sialic acid binding (2, 3 EA HA LAIV). The WT HA LAIV bound α2, 6 sialic compared to the EA HA LAIV and 2, 3 EA HA LAIV which both demonstrated an increased preference for α2, 3 sialic acid. On MDCKs, the WT HA and EA HA LAIVs showed similar replication at 32 °C but at 37 °C the EA HA LAIV replicated to lower infectious virus titers. The 2, 3 EA HA LAIV replicated poorly at both temperatures. This replication phenotype was similar on human nasal epithelial cell (hNEC) cultures, however the WT HA LAIV induced the highest amount of IFN-λ and infected more nasal epithelial cells compared to the other viruses. Together, these data indicate that egg adaption mutations in the HA protein that confer preferential α2, 3 sialic acid binding may adversely affect LAIV replication and contribute to reduced vaccine efficacy.